PENGARUH WORK-LIFE BALANCE KOMPENSASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Mahadiva, Made; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Employees are the most important factor that contributes to the achievement of company goals. Through employees, strength or resources will be obtained for the sustainability of the company. Work-life balance is an important thing to note so that employees feel they have a sense of desire to stay in their organization. This study aims to analyze the effect of Work life-balance, compensation, and job satisfaction on organizational commitment. This research was conducted at PT Agung Automall Gianyar by analyzing work-life balance, compensation, job satisfaction, and organizational commitment within the company. The sample in this study consisted of employees of PT. Agung Automall Gianyar, which consisted of 72 people who were determined based on the saturated sampling technique. To obtain the data needed in this study, interview methods and filling out questionnaires were used which were filled out by company employees. The data analysis technique used is the Classical Assumption Test, F-Test and T- Test. The results of this study indicate that the variables studied, namely work life balance, compensation and job satisfaction have a positive and significant impact on the organizational commitment of PT. Agung Automall Gianyar.